How terrorism ends understanding the decline and demise of terrorist campaigns - Cronin, Audrey Kurth 1958- (Princeton University Press, 2009)
Only by understanding the common ways in which terrorist movements have died out or been eradicated in the past can we hope to figure out how to speed the decline of today's terrorist groups, while avoiding unnecessary fears and costly overreactions. In How Terrorism Ends, Audrey Kurth Cronin examines how terrorist campaigns have met their demise over the past two centuries, and applies these enduring lessons to outline a new strategy against al-Qaeda. --from publisher description